The Expiry Registry of the Seizure Precautionary Measures in Form of Inscription and Mortgages - Siguas Rivas, M. Julián (2015)
Over the years, the application of the law 26639 was restricted as seizure, for the 28473 law published in the official newspaper El Peruano on 18 March 2005, to modify the text full of the article 625 of the Civil Procedure Code, establishing that the process initiated with the code of civil procedure of 1912 the measure precautionary was winding down of fully entitled to the five years since its implementation; i.e. were excluded the possibility thereafter expire seizure locked in procedures to be followed with the Civil procedure code. To same fate underwent coercive seizure listed under the scope of the tax code, since by order of D. Leg. 953 published in the official journal El Peruano on 5 February 2004, established that the precautionary measures locked under the scope of the tax code were not subject to expiration date, thus alluding to the 26639 law.